2023
DOI: 10.1177/15248380231178754
|View full text |Cite
|
Sign up to set email alerts
|

Victims of Technology-Assisted Child Sexual Abuse: A Scoping Review

Katrin Chauviré-Geib,
Jörg M. Fegert

Abstract: Over the past two decades, technology-assisted child sexual abuse (TA-CSA) has become the focus of attention in politics, legislation, society, as well as research. However, the majority of literature and studies focus primarily on the offenders. This scoping review therefore aims to illustrate how victims of TA-CSA are represented in studies as primary participants. The databases Embase, PsychInfo, PSYNDEX, Cochrane Library, and Web of Science as well as reference lists were searched. Studies needed to be pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In one of the few studies that have examined the progression from online to offline contact, Finkelhor and colleagues [ 8 ] found that 19% of their sample of 1501 youth between the ages of 10 and 17 reported online solicitation, but only 3% involved attempted or had actual offline contact by telephone, by mail, or in-person. In a scoping review, Chauviré-Geib and Fegert [ 23 ] used the term technology-assisted child sexual abuse (TA-CSA) as “a collective term to describe the use of technology in abuse” (p. 2), and they only found three qualitative studies that described the progression from online to offline sexual grooming and abuse in some of the cases [ 24 ]. While sex trafficking of minors is often seen as distinct from CSA, there is increasing evidence that minors are being recruited online for offline trafficking.…”
Section: The Role Of Technology In Offline Sexual Abusementioning
confidence: 99%
“…In one of the few studies that have examined the progression from online to offline contact, Finkelhor and colleagues [ 8 ] found that 19% of their sample of 1501 youth between the ages of 10 and 17 reported online solicitation, but only 3% involved attempted or had actual offline contact by telephone, by mail, or in-person. In a scoping review, Chauviré-Geib and Fegert [ 23 ] used the term technology-assisted child sexual abuse (TA-CSA) as “a collective term to describe the use of technology in abuse” (p. 2), and they only found three qualitative studies that described the progression from online to offline sexual grooming and abuse in some of the cases [ 24 ]. While sex trafficking of minors is often seen as distinct from CSA, there is increasing evidence that minors are being recruited online for offline trafficking.…”
Section: The Role Of Technology In Offline Sexual Abusementioning
confidence: 99%
“…It is not limited to behaviors such as penetration and sexual touching but can also occur in the online environment.Child sexual abuse is de ned as actions that occur through coercion, threat, or deception by an adult with the intention of ful lling their sexual desires, involving a child who is considered incapable of comprehending sexual intercourse and is not sexually mature (9, 10). Indeed, online sexual abuse, in particular, encompasses risky behaviors that children encounter in the online environment and can have negative effects on children (11). When examining the de nition of online sexual abuse in the literature, it becomes apparent that there is a concept confusion, and it has been attempted to be explained through various de nitions.…”
mentioning
confidence: 99%
“…When examining the de nition of online sexual abuse in the literature, it becomes apparent that there is a concept confusion, and it has been attempted to be explained through various de nitions. In a systematic review of online sexual abuse published in 2023, where 570 articles were screened, and 20 articles were compiled, the authors of the study suggested using the term "technology-facilitated child sexual abuse" to encompass all sexual acts involving children that occur through the use of technology (11). Sexting, also known as sexual messaging, is a broad term that encompasses the sending, receiving, or forwarding of sexual text messages, nude pictures, and/or sexually explicit photos and videos through digital technologies and applications such as social media platforms (12).…”
mentioning
confidence: 99%